Blood glucose levels should be considered as a new vital sign indicative of prognosis during hospitalization. Issue 1 (January 2021) - Kesavadev, Jothydev; Misra, Anoop; Saboo, Banshi; Aravind, S.R.; Hussain, Akhtar; Czupryniak, Leszek; Raz, Itamar
Abstract: Background and aims: The measurement of vital signs is an important part of clinical work up. Presently, measurement of blood glucose is a factor for concern mostly when treating individuals with diabetes. Significance of blood glucose measurement in prognosis of non-diabetic and hospitalized patients is not clear. Methods: A systematic search of literature published in the Electronic databases, PubMed and Google Scholar was performed using following keywords; blood glucose, hospital admissions, critical illness, hospitalizations, cardiovascular disease (CVD), morbidity, and mortality. This literature search was largely restricted to non-diabetic individuals. Results: Blood glucose level, even when in high normal range, or in slightly high range, is an important determinant of morbidity and mortality, especially in hospitalized patients. Further, even slight elevation of blood glucose may increase mortality in patients with COVID-19. Finally, blood glucose variability and hypoglycemia in critically ill individuals without diabetes causes excess in-hospital complications and mortality. Conclusion: In view of these data, we emphasize the significance of blood glucose measurement in all patients admitted to the hospital regardless of presence of diabetes. We propose that blood glucose be included as the "fifth vital sign" for any hospitalized patient. Highlights: We reviewed various impacts of elevated blood glucose in ambulatory and hospitalized subjects. Glycemic variability, even a high normal blood glucose range lead to morbidity and mortality in non-diabetic patients. Blood glucose should be tested in all patients who are hospitalized, and should be considered as a "fifth vital sign".